Prevalence, risk factors and clinical presentations of patients with peripheral vertigo: a retrospective study from a tertiary care hospital - Rahul, Raveendran Krishnan; Andrews, Chakramakal Joseph; Karuthedath Sridevi, Karuthedath Sridevi; Vinayakumar, Arayamparambil Rajagopalan (International Journal of Advances in Medicine, 2017)
Background: A retrospective study was conducted to find out the clinical presentations and risk factors of peripheral vertigo. Methods: Sixty patients with peripheral vertigo (age 20-79 years) who had presented with signs of vertigo were included in the study. A thorough history was taken from the subjects. The prevalence, clinical presentations and risk factors were subjected to statistical analysis. Results: Total 60 patients of age 20-79 years (15 males and 45 females) were included in the study. Based on the distribution of risk factors, age group 40-59 was highest followed by the age group of 60-79. The prevalence of incidence was significantly found in females (P < 0.01). The clinical manifestations presented were spinning, about to faint, light-headiness, disequilibrium and both spinning and about to faint. Spinning plus about to faint was significantly (p < 0.01) found as the major clinical manifestation with a female dominance (19/25). This was highly significant (p < 0.05) in the age group of 40-59 years (8/19). Disequilibrium (10%) was the least clinical presentation. Among the risk factors, the patient with ear infection was significantly found (31.6%) with predominance for female (12/19). Conclusions: The result concluded that prevalence of incidence was significantly found in females of age group 40-59 with clinical presentation of both spinning and about to faint. Risk factor of ear infection was significantly found. These observations will help a surgeon to recognize which all patients need inpatient management or emergency intervention. Furthermore, the need for awareness about the prompt treatment of ear infection is emphasized.